Longitudinal understanding of prognosis among adolescents with cancer. Issue 3 (15th December 2020) - Fisher, Rachel S.; Kenney, Ansley E.; Fults, Marci Z.; Manring, Samantha; Rodriguez, Erin M.; Desjardins, Leandra; Rausch, Joseph R.; Young‐Saleme, Tammi; Ranalli, Mark A.; Vannatta, Kathryn; Compas, Bruce E.; Gerhardt, Cynthia A.
Abstract: Objective: Despite calls to increase prognosis communication for adolescents with cancer, limited research has examined their perceptions of prognosis as compared with their parents. We assessed adolescents' understanding of their prognosis relative to parents and oncologists. Methods: Families of adolescents (aged 10‐17) were recruited at two pediatric institutions following a new diagnosis or relapse. Seventy‐four adolescents, 68 mothers, and 40 fathers participated at enrollment; 76 adolescents, 69 mothers, and 35 fathers participated one year later. The adolescent's primary oncologist reported on prognosis only at enrollment. Participants rated the likelihood of the adolescent's survival in five years, as well as reporting prognosis communication and sources of information. Results: Most oncologists (65%) and fathers (63%) discussed prognosis in numerical terms with the adolescent at baseline, which was greater than mother report (49%) of discussions of numerical prognosis with adolescents. Adolescents reported a better prognosis than oncologists, but comparable with mothers at diagnosis and one year. Adolescents' prognosis estimates were stable over time ( P > .05). At diagnosis, adolescent‐father ( P = 0.025) and adolescent‐oncologist ( P < 0.001) discrepancies were larger for youth with advanced than non‐advanced cancer. Adolescents whose parents received numerical prognosis estimates from the oncologist, and whose fathers reported providing numerical prognosis estimates had more accurate understandings of prognosis ( P < 0.05). Conclusions: Adolescent prognosis estimates were comparable with those of parents at diagnosis and one year but more favorable than that of oncologists. Although additional research is needed, results suggest discrepancies in prognosis estimates between family members and oncologists, particularly for adolescents with advanced cancer.